2019
DOI: 10.15640/jehd.v8n4a3
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the Impact of Social Loafing through the use of Team Charters and Team Evaluations

Abstract: In many university courses students work in teams on class activities, papers and projects. Instructors often choose the team method as students will be expected to work in teams in many of their jobs. Team-based activities facilitate cooperative learning which occurs when individuals work together to accomplish a common goal. Collaboration amongst team members can occur in both face-to-face settings and in online environments. Teaching students the skills needed to collaborate in both environments helps prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A semester-long team project gives students the opportunity to collaborate with others, organize their schedules, communicate with members in both written and oral form, work with and meet deadlines, demonstrate their work ethic, and be professional in their interactions within the group and with the instructor. Students can be given opportunities to lead portions of the project which can be assisted with a team charter that establishes norms of expected behavior on the team, allocates responsibilities, sets deadlines, and indicates what consequences will be for not meeting group expectations (Johnson & Horn, 2019). For example, GANTT charts allow students to envision an entire project's timing and when activities need to occur.…”
Section: Project Managementmentioning
confidence: 99%
“…A semester-long team project gives students the opportunity to collaborate with others, organize their schedules, communicate with members in both written and oral form, work with and meet deadlines, demonstrate their work ethic, and be professional in their interactions within the group and with the instructor. Students can be given opportunities to lead portions of the project which can be assisted with a team charter that establishes norms of expected behavior on the team, allocates responsibilities, sets deadlines, and indicates what consequences will be for not meeting group expectations (Johnson & Horn, 2019). For example, GANTT charts allow students to envision an entire project's timing and when activities need to occur.…”
Section: Project Managementmentioning
confidence: 99%
“…While working in a group is a necessary skill for survival in marketing, being able to demonstrate the ability to work by oneself is also necessary (Mackenzie, 2021;Schlee & Karns, 2017). Working independently in a team can be assisted by the use of team that assign tasks and hold students accountable for a specific portion of a project (Johnson & Horn, 2019).…”
Section: Strong Work Ethicmentioning
confidence: 99%
“…• Rewarding both group and individual effort [29] • Assigning instrumental and equitable tasks to all team members; an instrumental task is one that is indispensable to the team's project so that each team member believes that an adequate collective performance depends on his or her personal contribution [29] • Conducting peer evaluations [30] • Having each team adopt a written team charter [30]. (This is similar to the group rules and processes found that correlate with teamwork satisfaction [16] and the team expectations document [31].…”
Section: Conflict-resolution Skillsmentioning
confidence: 99%
“…Although experiential exercises are necessary, students want hard copy to read and study [11]. For example, students can be provided with a handout ("Coping with Hitchhikers and Couch Potatoes on Teams") analyzing example situations involving social loafing [30]. Al-Hammoud et al [32] introduced task, process, and relationship conflicts plus strategies to help mitigate or resolve personal conflict, including when and why these different types of conflicts occur, when they are productive or destructive, and how differences among team members' needs and perspectives may lead to conflict.…”
Section: Teaching Conflict Resolution Skills In Work Teamsmentioning
confidence: 99%
See 1 more Smart Citation